Biomass formation and sugar release efficiency of Populus modified by altered expression of a NAC transcription factor. (12th August 2022) - Payyavula, Raja S.; Badmi, Raghuram; Jawdy, Sara S.; Rodriguez, Miguel; Gunter, Lee; Sykes, Robert W.; Winkeler, Kimberly A.; Collins, Cassandra M.; Rottmann, William H.; Chen, Jin‐Gui; Yang, Xiaohan; Tuskan, Gerald A; et al.
Abstract: Woody biomass is an important feedstock for biofuel production. Manipulation of wood properties that enable efficient conversion of biomass to biofuel reduces cost of biofuel production. Wood cell wall composition is regulated at several levels that involve expression of transcription factors such as wood‐/secondary cell wall‐associated NAC domains (WND or SND). In Arabidopsis thaliana, SND1 regulates cell wall composition through activation of its down‐stream targets such as MYBs. The functional aspects of SND1 homologs in the woody Populus have been studied through transgenic manipulation. In this study, we investigated the role of PdWND1B, Populus SND1 sequence ortholog, in wood formation using transgenic manipulation through over‐expression or silencing under the control of a vascular‐specific 4‐ coumarate ‐CoA ligase ( 4CL ) promoter. As compared with control plants, PdWND1B ‐RNAi plants were shorter in height, with significantly reduced stem diameter and dry biomass, whereas there were no significant differences in growth and productivity of PdWND1B over‐expression plants. Conversely, PdWND1B over‐expression lines showed a significant reduction in cellulose and increase in lignin content, whereas there was no significant impact on lignin content of downregulated lines. Stem carbohydrate composition analysis revealed a decrease in glucose, mannose, arabinose, and galactose, but an increase in xylose in the over‐expression lines. Transcriptome analysis revealed upregulation of several downstream transcription factors and secondary cell wall related structural genes in the PdWND1B over‐expression lines, partly explaining the observed phenotypic changes in cell wall chemistry. Relative to the control, glucose release efficiency and ethanol production from stem biomass was significantly reduced in over‐expression lines. Our results show that PdWND1B is an important factor determining biomass productivity, cell wall chemistry and its conversion to biofuels in Populus .